Effect of pyrolysis temperature on the physicochemical properties of biochar derived from spent coffee grounds - Tran, Oanh Thi Kim; Truong, Toan Quoc; Phan, Luu Thi Kim; Nguyen, Din Van; Nguyen, Hong Thi Thu (International Journal of Sustainable Energy and Environmental Research, 2025)
Biochar is a carbon-rich material widely recognized for its ability to enhance soil quality, adsorb heavy metals, and sequester carbon, thereby contributing to pollution mitigation and the reduction of greenhouse gas emissions. Spent coffee grounds (SCG), an abundant agricultural byproduct, represent a promising feedstock for biochar production. While coffee ground-derived biochar (CBC) supports waste reduction and aligns with sustainable development and circular economy principles, a significant volume of SCG remains underutilized globally, particularly in Vietnam, one of the world’s leading coffee producers. Therefore, this study aims to investigate the influence of pyrolysis temperature on the physicochemical properties of CBC to identify optimal conditions for improving its environmental applications. SCG collected from coffee stores in Vietnam was subjected to slow pyrolysis under anoxic conditions at five different temperatures: 300°C, 350°C, 400°C, 450°C, and 500°C, with a fixed residence time of 2 hours. The obtained biochar samples were analyzed for yield, moisture content, ash content, pH, and surface functional groups. The findings revealed that increasing the pyrolysis temperature led to a decrease in both biochar yield and moisture content, while ash content and pH values increased accordingly. Fourier transform infrared analysis revealed significant differences in surface functional groups between SCG and CBC across different pyrolysis temperatures, highlighting the critical role of temperature in shaping biochar properties for adsorption and environmental remediation. The study contributes to a deeper understanding of how pyrolysis conditions influence the quality of SCG-derived biochar and offers a basis for optimizing production parameters to tailor its characteristics for specific applications.